Influence Of Consumption Of Katuk Leaves, Spinach And Cassava Against The Prosuction Of Breast Milk In Nursing Mothers In The Working Area Of Puskesmas Cilograng Year 2022 - Iis Siti Nirmalayanti; Wintarsih Wintarsih (International Journal of Health and Pharmaceutical (IJHP), 2023)
Based on the Global Breastfeeding Scorecard report which evaluates breastfeeding data from 194 countries, the percentage of infants under 6th month who are exclusively breastfed is only 40%. In addition, only 23 countries have exclusive breastfeeding rates above 60% (United Nations Children's Fund). However, at the Lebak district level, in 2019 there were 2553 babies and in 2020 there were 1.614 babies who were exclusively breastfed.This study aims to determine the Effect of Consumption of Katuk Leaves, Spinach and Cassava on the Production of Breastfeeding Mothers in the Work Area of ​​the Cilograng Health Center in 2022.This research method uses a Quasi Experiment research type with a pre and post test design without control. The population in this study were postpartum mothers and breastfeeding mothers in the period December 2021-August 2022 in the working area of ​​the Cilograng Health Center, a total of 433 people, 39 respondents as a sample, 13 for the katuk leaf consumption group, 13 for spinach leaf consumption and 13 respondents in the cassava leaf consumption group. . Respondents will be taken by accidental sampling technique. Data were analyzed using univariate, bivariate and multivariate analysis.The results of this study showed that most of the respondents were aged 20-35 years (87.2%), more than half of the respondents had multipara/grandemultipara parity status (69.2%) and half of the respondents had secondary education (56.4%). In the katuk leaf group (pvalue 0.003), spinach leaf group (pvalue 0.003) and cassava leaf group (pvalue 0.001) where the pvalue of the three groups was > 0.05, it could be interpreted that these three groups had an effect on milk production in nursing mothers.It can be concluded that katuk, spinach and cassava leaves can help milk production in nursing mothers. It is hoped that this research can educate the public more with the aim of maintaining and increasing the rate of exclusive breastfeeding in the Working Area of ​​the Cilograng Health Center.